The Aleut language, the elements of Aleut grammar with a dictionary in two parts containing basic vocabularies of Aleut and English, by Richard Henry Geoghegan; edited by Fredericka I. Martin. - Geoghegan, Richard Henry, 1866-1943. (Washington, D. C., United States Dept. of the interior, 1944)
iii, 169 p.